In situ formation of Imidazole-Based 2D interlayer for efficient perovskite solar cells and modules - Kim, Jun Young; Han, Gill Sang; Lee, Jae Myeong; Mun, Seunguk; Gong, Oh Yeong; Sohn, Chang Hwun; Park, Gyuna; Cho, In Sun; Kim, Yunseok; Kim, Dong Hoe; Jung, Hyun Suk (International Journal of Energy Research, 2022)
After overcoming 25% of the power conversion efficiency (PCE) for the perovskite solar cells (PSCs), lots of efforts are being put into modularization. In order to advance this, the development of passivation materials that can operate effectively without affecting the cell areas is essential. This study introduces the 1-decyl-3-methylimidazolium bromide (DMIMB), which is an imidazole-based passivator, working well to form a uniform 2D interlayer on the perovskite surface regardless of the cell area. Consequently, perovskite films that adopted DMIMB 2D interlayer employed perovskite film showed less trap density, more suitable Fermi level, which led to efficiency enhancement up to the PCE of 22.40%. Furthermore, the DMIMP enables the scalable PSCs, resulting in 18.43% of PCE for perovskite solar modules (PSMs) in the active area of 22.6 cm2.
Keywords: 2D layer; Band energy; Band energy level alignment; Defect passivation; Energy level alignment; Imidazol; Imidazole-base ionic liquid; Surface defect passivation; Wide-band-gap; Wide-bandgap 2d layer; band energy level alignment; hybrid perovskite solar cells; imidazole-base ionic liquid; surface defect passivation; wide-bandgap 2D layer